Penanganan edentulus total rahang atas yang dengan disertai denture-induced hyperplasia Management of total maxillary edentulous with denture-induced hyperplasia - Elizabeth Mailoa; Peter Rovani; Edy Machmud (Journal of Dentomaxillofacial Science, 2012)
Lesions caused by traumatic or unbalance occlusion, and overextension denture may occur in the majority ofpatients who use denture. This generally occurs in the use of unfit full dentures (FD) and in a long period of timecausing chronic irritation to mucosal tissues caused by the sharp and overextension of the FD flange. One of themost common tissue reaction caused by using unfit FD is inflammatory fibrous hyperplasia or more commonlyknown as the flabby ridge. This tissue reaction appears as fold of mucosal tissue, single or multiple, growexcessively around the sulcus mucobuccal, on the mucosa area unite gingiva and the cheek mucosa. Movement andgrowth of the tissue continuously causes problems in maintaining retention of FD. This article reports themanagement of denture-induced hyperplasia on maxilla edentulous of a 65-year old woman. Hyperplasia occurredfrom the left premolar to right premolar region of the maxilla. Excision was carried out through a 7 cm length tissueand then made for a conventional FD. As the result, patients are satisfied with the use of the new FD and did notfeel any further disruption to mucosal tissues